Bahan Ajar IPA Berbasis Etnosains Tema Pemanasan Global untuk Peserta Didik SMP Kelas VII (UPEJ Unnes Physics Education Journal, 2019)
This research aims is to develop ethnoscience based teaching materials with the theme of global warming for seventh grade junior high school students. The research method used is Research and Development (R & D) wich includes several stages: problem identification, data collection, design science teaching material based ethnoscience, design validation, design revisions, smale scale trials, revision science teaching materials, large scale trials, and final science teaching materials. The subjects of the research trial were students of class VII D SMP N 30 Semarang in the academic year 2018/2019. Sampling using purposive sampling technique. Advisability and readability test using questionnaires and passenger tests. Test of increasing cognitive learning outcomes using Pretest-Posttest Control Group Design, while affective learning outcomes use affective questionnaire. The gain test of cognitive learning outcomes gets an average score of 0,46, while the gain test for affective learning results gets an average score of 0,19. These results indicate that there is an increase in cognitive and affective learning outcomes for students who use ethnoscience based science teaching materials